Analisis Faktor-Faktor Penghambat Total Quality Management Terhadap kualitas Pekerjaan Programmer PT XYZ - Andika Fauzi Hadiana; Intan Widuri Sakti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This qualitative study analyzes barriers to Total Quality Management (TQM) implementation affecting programmer work quality at PT XYZ, a software development company certified with ISO 9001:2015. Using a descriptive case study approach, data were collected through in-depth interviews with seven informants and supported by secondary data including QA reports, internal audit results, SDLC audits, and training records from 2021–2025. Data analysis applied the Miles and Huberman model, supported by Fishbone Diagram and SWOT analysis. The study focuses on four TQM dimensions: management commitment, employee involvement, training and development, and continuous improvement. Findings indicate that TQM implementation barriers are interrelated, including weak enforcement of quality standards due to deadline pressure, limited employee involvement, inconsistent training programs, and ineffective PDCA cycles. These barriers negatively affect programmer work quality, reflected in recurring CAPA findings, increased audit non-conformities, high bug rates, declining code quality ratings, and skill gaps among programmers. The study recommends strengthening management commitment, enhancing employee involvement, establishing continuous training programs, and optimizing systematic continuous improvement practices to sustainably improve programmer work quality.